Pemanfaatan Mikrokontroler AVR untuk Pengendalian Sejumlah Parameter Fisis pada Analogi Smartgreenhouse - Bayu Arief Prakoso; Arief Goeritno; Bayu Adhi Prakosa (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2020)
A number of physical parameters are related to the air temperature and humidity in the room, soil humidity, and the presence of light. All physical parameters are used to measure the performance of the control system based-on ATmega32 microcontroller. The measurement results of the control system performance are then sent and displayed on an Android-based device to find out the performance of the sending and receiving data system assisted by the Bluetooth protocol network. The measurement result of room temperature values is ranging of 26-36 0C and the humidity is ranging of 54-74%. Measurement result against the soil moisture parameter is 85% that obtained from the conversion of 3 volts dc in 8-bit digital data, while the soil humidity at normal condition is 60%.The presence light sensor when not detecting light, the sensor output value of 5 volts dc is converted into 256 scales digital data. For this condition, the controller sends a signal of 256 scales or maximum output to the actuator for energizing the lamp, so that maximum light can be produced. Assisted by Android-based smartphone and Bluetooth protocol network for sending and receiving data display based-on the measurement and monitoring of a number of physical parameters, so that it is the suitability of the display that produced by the control system based-on ATmega32 microcontroller.